Business Strategy of New Entrants in Telecommunications Industry : Case Study from Malaysia - Hue, Fatt Seng (2012)
Since the year 2000, the Malaysian mobile communications industry has seen Rapid and dynamic changes with multiple new entrants entering the industry and competing against the Incumbents for market share and revenue. With more than ten players competing in this institutionalized industry, and with its market size and saturated market penetrations, it is considered highly competitive. In this study, the business strategy of new entrants will be evaluated. This study identified the institutional pressures and the strategic responses of new entrants in the industry in the face of these pressures. Advancing the analysis on their strategic responses, the study identified the resources Developed and deployed by the new entrants that facilitated their respective strategic pursuit.